The Impact of the 2011 Rugby World Cup on the Collaborative Capacity of Organisations in Regional Tourism Destination Marketing Networks - Werner, K (New Zealand Association of Event Professionals (NZAEP), 2013)
Prior to the 2011 Rugby World Cup (RWC 2011), the need for effective partnerships and the development of high quality relationships between organisations involved in the event was consistently highlighted. This research explores the impact of RWC 2011 on Tourism Auckland’s ability to collaborate with organisations within the Auckland region as well as with other regional tourism organisations throughout New Zealand. Data for this research was collected from sixty-nine semi-structured interviews with CEOs and senior managers conducted both pre-event and post-event. A formal survey and corporate documents were also relied upon. The findings demonstrate that the impact of RWC 2011 was more profound in intra-regional collaboration as opposed to inter-regional collaboration. The research identifies the main conditions necessary for increased CC in the mega-events context: clear and common goals (and shared vision); a collaborative approach; regular, clear communication; honesty and openness; trust; the integration of all stakeholders; empathy; and leadership. Overall, the results suggest that mega-events can increase collaboration and collaborative capacities of organisations involved. Careful strategic pre-event planning, the integration of all relevant stakeholders, and a unifying collaborative approach are essential conditions.